MODULATION STRATEGY IN TRANSLATING VERB PHRASES IN ENGLISH COOKBOOK INTO INDONESIAN - Kadek Ayu Ekasani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This research is focused on the modulation strategy in translating verb phrases in English cookbook into Indonesian. The data used in this study is taken from English cookbook entitled “The Essential Book of Sauces & Dressings” written by Murdoch Books and published by Periplus, Singapore and the translation into Indonesian entitled “Saus dan Dressing yang esensial” translated by Hadyana P. and published by Periplus, Indonesia. The main theory is adopted from the book “A Text book of Translation” by Newmark (1988) about the translation strategy. The methods that are used to collect data are documentation and observation. The results of this study not only found a number of independent modulation translation strategys, but there was also a combination of the modulation translation strategy with other strategys, including modulation and transposition; literal translation and modulation; modulation and reduction; transposition, modulation and calce; modulation, addition and transposition.